2010
DOI: 10.1175/2010jas3490.1
|View full text |Cite
|
Sign up to set email alerts
|

Regime of Validity of Soundproof Atmospheric Flow Models

Abstract: Ogura and Phillips derived the original anelastic model through systematic formal asymptotics using the flow Mach number as the expansion parameter. To arrive at a reduced model that would simultaneously represent internal gravity waves and the effects of advection on the same time scale, they had to adopt a distinguished limit requiring that the dimensionless stability of the background state be on the order of the Mach number squared. For typical flow Mach numbers of M ; 1 /30, this amounts to total variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 13 publications
1
70
0
2
Order By: Relevance
“…The governing equations underlying the local area edge-based model adopt the Lipps-Hemler nonhydrostatic anelastic system [16,17], suitable for simulation of a broad range of atmospheric flows [13,37]. For dry dynamics addressed in this paper, these equations govern the evolution of momentum and entropy, constrained by the incompressible-like mass continuity equation.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The governing equations underlying the local area edge-based model adopt the Lipps-Hemler nonhydrostatic anelastic system [16,17], suitable for simulation of a broad range of atmospheric flows [13,37]. For dry dynamics addressed in this paper, these equations govern the evolution of momentum and entropy, constrained by the incompressible-like mass continuity equation.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The collaborative work between Rupert Klein (Free University of Berlin), Piotr Smolarkiewicz and colleagues (Klein et al 2010) provided a multiple scale analysis showing that the regime of validity of the two soundproof models (the anelastic LippsHemler and pseudo-incompressible Durran models) covers stratification strengths corresponding to realistic variations of potential temperature < 30 degrees across the pressure scale height. This extends the classical results of Ogura and Phillips (1962) by two orders of magnitude.…”
Section: Regime Of Validity Of Soundproof Atmospheric Flow Modelsmentioning
confidence: 99%
“…Clearly, EULAG is proven capable of resolving small-scale internal waves in global simulations being driven by planetary wave instability, that is, the results are clearly multiscale. We believe this capability is due to model design (non-oscillatory forward-intime numerics and implicit treatment of potential temperature perturbation) as well as an inherent ability of the anelastic model to successfully capture multiscale effects between synoptic and mesoscale waves (Klein et al 2010).…”
Section: Resolution Of Smaller Scale Gravity Waves In Held-suarez Simmentioning
confidence: 99%
“…Recent steps in this direction have been taken for the anelastic and pseudo-incompressible models. Using the method of distinguished limits, Klein et al (2010) demonstrated that for realistic values of atmospheric stratification (∆θ ∼ 50 K over 15 km depth), both the LH anelastic and pseudo-incompressible models are true multi-scale, sound-proof models in that they feature two asymptotically separated time scales (geostrophic advection and internal gravity waves). The requirement for sound-proof gravity waves to evolve asymptotically closely to compressible gravity waves is H p /H θ < O(M 2/3 ), where H p is the pressure scale height and M is the Mach number.…”
Section: Remarksmentioning
confidence: 99%